Efficacy and Safety of Oral Administration of a Mixture of Probiotic Strains in Patients with Psoriasis: A Randomized Controlled Clinical Trial - Vicente Navarro-López; Asunción Martínez-Andrés; Ana Ramírez-Boscá; Beatriz Ruzafa-Costas; Eva Núñez-Delegido; Miguel A. Carrión-Gutiérrez; David Prieto-Merino; Francisco Codoñer-Cortés; Daniel Ramón-Vidal; Salvador Genovés-Martínez; Empar Chenoll-Cuadros; José M. Pérez-Orquín; et al. (Medical Journals Sweden, 2019)
The aim of this 12-week randomized, double-blind, placebo-controlled trial was to determine the efficacy and safety of a probiotic mixture in the reduction of psoriasis severity. Ninety 18-70-year-old adults with plaque psoriasis were randomized into probiotic and placebo groups. At 12-week follow-up, 66.7% of patients in the probiotic group and 41.9% in the placebo group showed a reduction in Psoriasis Area and Severity Index of up to 75% (p < 0.05). A clinically relevant difference was observed in Physician Global Assessment index: 48.9% in the probiotic group achieved a score of 0 or 1, compared with 30.2% in the placebo group. The results of follow-up 6 months after the end of the study showed a lower risk of relapse after the intake of the probiotic mixture. Analysis of gut microbiota confirmed the efficacy of the probiotic in modulation of the microbiota composition.